La Gimnasia Musical Aerobica Comunitaria. Propuesta De Un Programa Alternativo De Orientación Para La Promoción De Salud En La Comunidad “El Paraíso - Aguinda Shiguango, Jessica Yajaira (2016)
The subject of the following research LA GIMNASIA MUSICAL AEROBICA COMUNITARIA. PROPUESTA DE UN PROGRAMA ALTERNATIVO DE ORIENTACIÓN PARA LA PROMOCIÓN DE SALUD EN LA COMUNIDAD “EL PARAÍSO”. Which presents the following problem How will an Alternative Guidance Orientation Program for health promotion in the "El Paraíso" community of the Canton of Tena in the province of Napo ?, whose general objective is to Design an Alternative Orientation Program for The health promotion based on the Aerobic Community Musical Gymnastics in the community "El Paraíso", of the Canton of Tena in the province of Napo. The specific objectives are: To diagnose the development of an Alternative Guidance Program for the improvement of health in the community "El Paraíso", of the Canton of Tena in the province of Napo. To evaluate the development of the physical work capacity in the population under study in the community "El Paraíso", of the Canton of Tena in the province of Napo. To design a proposal to solve the problem detected based on an Alternative Guidance Program for the improvement of health in the community "El Paraíso", in the Canton of Tena in the province of Napo. The design of the research is non-experimental, the methods used were inductive and deductive. The results of the research are shown in tables, graphs and the realization of an aerobic musical gymnastics program that is the consequence of the application of surveys and observation to the El Paraíso community; In the discussion of the research could be compared with data from other researchers. After analyzing the results it was concluded that the population of the community El Paraíso has bad habits such as sedentarism, ingestion of alcoholic beverages and tobacco, physical inactivity is deteriorating the state of health of the population, so it is recommended the application Of an aerobic musical gymnastics program in the Paradise community.